Washington View: Could American support for public education be slipping?. (October 2017) - Ferguson, Maria
According to this year's PDK Poll of the Public's Attitudes Toward the Public Schools, many parents would be willing to abandon public schools if a voucher were dangled before them. Has there really been a shift in American public opinion about public education or does the poll merely reflect what parents believe is best for their own child? The author concludes that some Americans may be poised to re-evaluate their long-standing commitment to public education if the price is right .